An unexpected case of bilateral kidneys studded with multiple abscesses, in a nondiabetic healthy woman-A case report - Kamble, Vijaya; Mitra, Kajal (Asian Journal of Medical Sciences, 2014)
Bilateral multiple renal abscesses have been found in individuals with predisposing factors but are infrequently encountered in otherwise healthy individuals. In our case , a lady presented with history of fever and chills with bilateral renal angle tenderness. Ultrasonography and computed tomography showed both kidneys to be studded with multiple renal abscesses of varying sizes. USG Guided percutaneous aspiration was done to establish the correct diagnosis and identify the causative micro organism. Her blood culture and urine culture were negative. The patient was successfully treated with combined intravenous and oral course of antibiotics. In conclusion, as contrary to the usual belief, bilateral renal abscesses can occur in a healthy individual without any history of diabetes or immunocompromised status. In addition full recovery is possible solely with antibiotics. DOI: http://dx.doi.org/10.3126/ajms.v6i3.10933 Asian Journal of Medical Sciences Vol.6(3) 2015 91-93